Intertextual Episodes in Lectures: A Classiﬁcation from the Perspective of Incidental Learning from Reading - Shaw, Philip; Irvine, Aileen; Malmström, Hans; Pecorari, Diane (HERMES - Journal of Language and Communication in Business, 2010)
In a parallel language environment it is important that teaching takes account of both the languages students are expected to work in. Lectures in the mother tongue need to offer access to textbooks in English and encouragement to read. This paper describes a preliminary study for an investigation of the extent to which they actually do so. A corpus of lectures in English for mainly L1 English students (from BASE and MICASE) was examined for the types of reference to reading which occur, classiﬁed by their potential usefulness for access and encouragement. Such references were called ‘intertextual episodes’. Seven preliminary categories of intertextual episode were identiﬁed. In some disciplines the text is the topic of the lecture rather than a medium for information on the topic, and this category was not pursued further. In the remaining six the text was a medium for information about the topic. Three of them involved management, of texts by the lecturer her/himself, of student writing, or of student reading. The remaining three involved reference to the content of the text either introducing it to students, reporting its content, or, really the most interesting category, relativizing it and thus potentially encouraging critical reading. Straightforward reporting that certain content was in the text at a certain point was the most common type, followed by management of student reading. Relativization was relatively infrequent. The exercise has provided us with categories which can be used for an experimental phase where the effect of different types of reference can be tested, and for observation of the references actually used in L1 lectures in a parallel-language environment.